Permasalahan Penerapan Klausula Pembatasan Pertanggungjawaban Dalam Perjanjian Terkait Hak Menuntut Ganti Kerugian Akibat Wanprestasi - M.P. Pangaribuan, Togi (Jurnal Hukum & Pembangunan, 2019)
One of the most common aspects in the development of the freedom of contract principle is the use of a clause limiting liability based on Article 1249 of the Indonesian Civil Code. In practice, the application of such clause is often times not in line with other principles under Indonesian contract law such as the principles of balanced, morals, and decency that are also inseparable from Indonesian contract law principles. This issue becomes even more apparent in cases where a breach of contract is done deliberately and/or grounded on bad faith of one of the parties that has calculated that the deliberate breach and the subsequent consequences would still deliver a profit to the party in breach. Taking reference from a case law in the Netherlands, adopting the principles of the old Dutch Commercial Code, it is suggested that clauses that limit a party’s liability can be waived if there are aspects of “gross negligence” in the performance of the contract